Theoretical Studies Regarding Corruption, Corruption Crimes, and Perspective Studies on Islamic Criminal Law Theory (Fiqh Jinayah) - Tagor Indra Mulia Lubis; Bagus Ramadi (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2023)
The purpose of this discussion is to know and understand the theory of corruption, criminal acts of corruption, and the principles of jinayah fiqh related to corruption. The analytical method used is to use literature studies originating from various online reference books and journals as well as several credible and relevant internet sites. The resulting discussion is about the definition of corruption as outlined by several experts, criminal acts of corruption, the legal basis for criminal acts of corruption, forms of terms in Islamic law that are synonymous with corruption, and efforts made to eradicate corruption.